Kesadaran Beragama Pelaku Pariwisata di Kawasan Malioboro - Wahyu Amin Arifudin; Nurul Fatihah; Ahmad Echsan; Lailatul Maftuhah; Difla Nadjih; Agus Pandoman (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2019)
This study identifies the religious awareness of informal sector tourism actors participating in the Malioboro Mengaji program in Yogyakarta. Qualitative descriptive research with a phenomenological approach is useful for getting a natural overview and views of informants. The data were collected by participatory observation and in-depth interviews. Most of the informants were middle-aged who had tasted the acid of life including all forms of deviations from religious teachings. The passage of age encourages the search for inner and outer happiness. One of them is by learning the Koran. The initial motivation behind the various participants experienced changes along with participation in the Al Quran reading training. The desire to realize a lighter life burden and peace of mind with a sense of pride in being able to directly read the Islamic holy book that is the guide of his life.